Energy-saving roadblock utilizing optical-electrical characteristic - HUANG YI (2014)
The utility model discloses an energy-saving roadblock utilizing an optical-electrical characteristic. The energy-saving roadblock comprises a base and a top cover, wherein a first groove is formed in the base; the top cover is spliced in the first groove, and is in matched connection with the base; mounting holes are further formed in the base; a foundation support is arranged in the middle of the inner side of the top cover; LEDs are arranged on the base; an energy storing device and a drive circuit are arranged on the base below the foundation support; a solar panel is arranged on the side surface of the top cover; a second groove is formed in the upper end of the top cover; a light-control circuit is arranged in the second groove; the solar panel is in electric connection with the energy storing device; the light-control circuit is in electric connection with the LEDs through the drive circuit; when a vehicle drives on urban and rural roads or expressways, light emitted from the energy-saving roadblock ca